Scalable single-step microfluidic production of single-core double emulsions with ultra-thin shells1. Issue 16 (21st August 2015) - Arriaga, L. R.; Amstad, E.; Weitz, D. A.
<x xml:space="preserve">Abstract</x> We report a scalable single-step microfluidic technique for the production of monodisperse double emulsions with very thin shell thicknesses, of about 5% of the drop radius.